PENGARUH KOMPENSASI, KOMUNIKASI, DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWANPADA PT. KARYA PUTRA KARIMUN (KPK) - Selviana Selviana; Wasiman Wasiman (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The effect of Compensation, Communication, and Occupational Safety on employee performance at PT Karya Putra Karimun (KPK). This research uses quantitative research methods. This study uses data from the distribution of questionnaires via a google form link to 107 employees of PT Karya Putra Karimun (KPK). The method of data collection using the saturated sampling technique method. This research uses statistical data analysis method using SPSS version 25. based on the results of the analysis that can show that simultaneously and partially no effect on compensation, communication and work safety on performance at PT. Karya Putra Karimun (KPK) with a calculated T value of 0.1826> 1.98326 on the compensation variable. for the communication variable has no effect on employee performance where T count -1.066 < t table 1.98326. While the work safety variable has no effect on employee performance at PT Karya Putra Karimun (KPK) of 1.701 < t table 1.98326. It can be seen from the results of the study that Compensation, Communication and Work Safety from one of the variables that affect only Compensation and does not affect Communication and Occupational Safety.